Characterization of the surface layer glycoprotein of Clostridium symbiosum HB25. - Messner, P (1990)
The cell surface of Clostridium symbiosum HB25 is covered by a squarely arranged surface layer (S-layer) glycoprotein. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the sodium dodecyl sulfate-soluble whole-cell extract showed the presence of several high-molecular-weight protein bands in a narrow range (approximate Mr, 140,000) which, upon periodic acid-Schiff staining, gave a positive reaction. After proteolytic degradation of the purified S-layer glycoprotein, a single glycopeptide fraction was obtained by gel permeation chromatography. Hydrolysis, treatment with aqueous hydrofluoric acid, and 1H and 13C nuclear magnetic resonance studies showed that the glycoprotein glycan is a high-molecular-weight polymer (approximate Mr, 15,000) of tetrasaccharide repeating units with the component sugars N-acetylgalactosamine (GalNAc), N-acetylmannosamine (ManNAc), and N-acetylbacillosamine (BacNAc; 2-N-acetyl-4-amino-2,4,6-trideoxy glucose) linked by monophosphate diesters. The following structure is proposed: [----6)-alpha-D-ManpNAc-(1----4)-beta-D-GalpNAc-(1----3)-alpha-D-+ ++BacpNAc- (1----4)-alpha-D-GalpNAc-(1----PO3)----]n. The nuclear magnetic resonance data provided evidence for a charge interaction between the free amino group of BacNAc and the phosphate group of adjacent glycan chains. Since polycationic ferritin did not label the cell surface of intact cells, an electrostatic interaction can also be expected in vivo, leading to a charge-neutral outer surface, which is characteristic of all other S layers from members of the family Bacillaceae studied so far.